2007
DOI: 10.1088/0960-1317/17/10/011
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of PLGA microvessel scaffolds with circular microchannels using soft lithography

Abstract: A simple micromolding method for fabricating PLGA (poly(lactic-co-glycolic acid)) microstructures made up of microchannels with a circular cross-section is presented. The thermal reflow technique is adopted to fabricate the semi-cylindrical photoresist master. The PLGA solution is prepared by dissolving PLGA polymer in acetone and then casting the solution onto the semi-cylindrical photoresist master to produce PLGA microstructures. Two PLGA membranes are bonded together to form microstructures consisting of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…Nanobiomaterial is one of the crucial fields in the study of nanobiotechnology. The major applications of nanobiomaterial are the fabrication of scaffolds for tissue engineering (Luis et al, 2007;Wang et al, 2007;Dalby et al, 2004) and carriers for drug delivery (Sonaje et al, 2007;Mittal et al, 2007;Ryu et al, 2007). The former refers to the fabrication of nanostructured patterns on a biomaterial through chemical processes.…”
Section: Introductionmentioning
confidence: 99%
“…Nanobiomaterial is one of the crucial fields in the study of nanobiotechnology. The major applications of nanobiomaterial are the fabrication of scaffolds for tissue engineering (Luis et al, 2007;Wang et al, 2007;Dalby et al, 2004) and carriers for drug delivery (Sonaje et al, 2007;Mittal et al, 2007;Ryu et al, 2007). The former refers to the fabrication of nanostructured patterns on a biomaterial through chemical processes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the classical circular cross sections, microfabrication also produces channels with noncircular cross sections, such as rectangular, elliptic, and trapezoidal which have wide practical applications in microelectromechanical systems (MEMS) [3,4]. The third most common microchannel geometry may be the semicircular profile, which occurs naturally in hard micromachining with isotropic etching [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…To solve the dead volume problem, the same group developed microvessel scaffolds with circular microchannels on both polydimethylsiloxane and PLGA substrates using the photoresist melting approach. 11,12 Borenstein et al have recently reported on the fabrication of another circular cross-sectional microvascular scaffold structure based on the polystyrene substrate. Successful seeding of primary human umbilical vein endothelial cells was observed.…”
Section: Introductionmentioning
confidence: 99%
“…This occurs due to absorption of the cultivation medium and the following hydrolysis, and makes it difficult to use optical microscopy to monitor the progress of cell seeding. 12 In addition, dynamic seeding can be carried out using a peristalsis pump to give the seeded cells properties similar to those of the endothelial cells of a real capillary. This is the commonly used cell culture method.…”
Section: Introductionmentioning
confidence: 99%